Perceptions about the Assessment in Emergency Virtual Education Due to COVID-19: A Study with University Students from Lima - Iván Montes-Iturrizaga; Gloria María Zambrano Aranda; Yajaira Licet Pamplona-Ciro; Klinge Orlando Villalba-Condori (MDPI AG, 2023)
The COVID-19 pandemic forced a large section of Peruvian universities to design systems for emergency virtual education. This required professors to quickly learn how to use teaching platforms, digital tools and a wide range of technological skills. In this context, it is remarkable that formative assessment may have been the pedagogical action with the greatest number of challenges, tensions and problems, due to the lack of preparation of many professors to apply performance tests and provide effective feedback. Given this, it is presumed that these insufficiencies (previously exhibited in face-to-face education) were transferred to virtual classrooms in the framework of the health emergency. A survey study was carried out on 240 students from a private university in Lima to find out their perceptions and preferences regarding the tests that their professors administered in the virtual classrooms. It was found that the students were assessed, for the most part, with multiple choice tests. In addition, it was found that the students recognized that the essay tests were the most important for their education, but they preferred multiple choice tests. Finally, it was found that law school students were mostly assessed with essay tests and psychology students with oral tests.